Extracellular polymeric substances of biofilms: Suffering from an identity crisis. (15th March 2019) - Seviour, Thomas; Derlon, Nicolas; Dueholm, Morten Simonsen; Flemming, Hans-Curt; Girbal-Neuhauser, Elisabeth; Horn, Harald; Kjelleberg, Staffan; van Loosdrecht, Mark C.M.; Lotti, Tommaso; Malpei, M. Francesca; Nerenberg, Robert; Neu, Thomas R.; et al.
Abstract: Microbial biofilms can be both cause and cure to a range of emerging societal problems including antimicrobial tolerance, water sanitation, water scarcity and pollution. The identities of extracellular polymeric substances (EPS) responsible for the establishment and function of biofilms are poorly understood. The lack of information on the chemical and physical identities of EPS limits the potential to rationally engineer biofilm processes, and impedes progress within the water and wastewater sector towards a circular economy and resource recovery. Here, a multidisciplinary roadmap for addressing this EPS identity crisis is proposed. This involves improved EPS extraction and characterization methodologies, cross-referencing between model biofilms and full-scale biofilm systems, and functional description of isolated EPS with in situ techniques (e.g. microscopy) coupled with genomics, proteomics and glycomics. The current extraction and spectrophotometric characterization methods, often based on the principle not to compromise the integrity of the microbial cells, should be critically assessed, and more comprehensive methods for recovery and characterization of EPS need to be developed. Graphical abstract: Image 1 Highlights: Extracellular polymeric substances feature in key societal problems (clinical, environmental). Methods and standards of EPS recovery and characterization need to be critically assessed. More emphasis should be placed on methods that enable identification (chemical and function). Integrated and multi-displinary analyses are required on biofilms and EPS isolates. Will improve biofilm management and enable a more circular economy in water and waste.